Evaluation and therapy outcome in children with auditory neuropathy spectrum disorder (ANSD). (December 2019) - Ehrmann-Müller, Désirée; Cebulla, Mario; Rak, Kristen; Scheich, Matthias; Back, Daniela; Hagen, Rudolf; Shehata-Dieler, Wafaa
Abstract: Objectives: The aims of the present study are to: describe diagnostic findings in patients with auditory neuropathy spectrum disorder (ANSD); and demonstrate the outcomes of different therapies like hearing aids (HAs) or cochlear implantation. Methods: 32 children were diagnosed and treated at our tertiary referral center and provided with HAs or cochlear implants (CIs). All of them underwent free-field or pure-tone audiometry. Additionally, otoacoustic emissions (OAEs), impedance measurements, auditory brainstem responses (ABRs), auditory steady-state responses (ASSR), electrocochleography, and cranial magnetic resonance imaging (cMRI) were all performed. Some patients also underwent genetic evaluation. Following suitable provision pediatric audiological tests, psychological developmental diagnostic and speech and language assessments were carried out at regular intervals in all the children. Results: OAEs could initially be recorded in most of the children; 17 had no ABRs. The other eight children had a poor ABR morphology. Most of the children had typical, long-oscillating cochlear microphonics (CMs) in their ABRs, which was also observed in all of those who underwent electrocochleography. Eight children were provided with a HA and 17 received a CI. The functional gain was between 32 and 65 decibel (dB) with HAs and between 32 and 50 dB with CI. A speech discrimination level between 35 and 100% was achieved during open-set monosyllabic word tests in quiet with HA or CI. With the Hochmair-Schulz-Moser (HSM) sentence test at 65 dB SPL (sound pressure level), 75% of the children with a CI achieved a speech discrimination in noise score of at least 60% at a signal to noise ratio (SNR) of 5, and four scored 80% or higher. Most of the children (72%) were full-time users of their devices. All the children with a CI used it on a regular basis. Conclusion: Only a few case reports are available in the literature regarding the long-term outcomes of ANSD therapy. The present study reveals satisfactory outcomes with respect to hearing and speech discrimination in children with CIs or HAs. The nearly permanent use of the devices reflects a subjective benefit for the children. Provision with a suitable hearing device depends on audiological results, the speech and language development of an individual child, and any accompanying disorders. Repeated audiological evaluations, interdisciplinary diagnostics, and intensive hearing and speech therapy are essential for adequate rehabilitation of this group of children.